Who benefits from postoperative ICU admissions?—more research is needed - Park, Chi-Min; Suh, Gee Young (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Postoperative complications increase mortality and reduce quality of life after surgery (1). Recently, numbers of elderly patients with severe comorbidity who are in need of a surgical service have increased, as well as the numbers of patients who are at risk of postoperative complications (2). Thus, health care systems should strive to reduce postoperative complications and mortality by improving postoperative care after elective surgery (1,3).